Separation Practices in Children and Adolescents Admitted for Suicidal Behavior: A National Survey of French Psychiatrists - Payet, Maymouna Mourouvaye; Bonfils, Nicolas A.; Ouss, Lisa; Fourcade, Lola J.; Touati-Pellegrin, Marie; Golse, Bernard; Cohen, Jérémie F.; Woestelandt, Laure (Frontiers in Pediatrics, 2022)
Objectives: To assess practices of French psychiatrists regarding their management of children and adolescents with suicidal behaviors, focusing on the use of a separation protocol in which the youths are separated from their relatives. Methods: In 2017, we conducted an online cross-sectional survey of French psychiatrists caring for children and adolescents. Participants were asked to describe their practice of a separation protocol in children and adolescents admitted for suicidal behavior. Our main descriptive analysis explored whether participant characteristics were associated with the use of a separation protocol. The response rate was 218/2403 (9.1%); 57.9 % of respondents worked in a University hospital, 60% of respondents reported routinely hospitalizing children. Results: A separation protocol was set up by 91.1% of survey participants (systematically 39.6%, on a case-by-case basis 51.5%). The mean age from which a separation protocol was indicated was above 11 years; 64% of participants reported a separation period of ≤ 48 hours. The most common (87%) criterion cited for establishing a separation period was family relationship difficulties. The most common (80.9%) reason to justify the use of a separation protocol was to allow a better clinical assessment. Exploratory analyses did not identify any participant characteristics associated with the use of a separation protocol (p > 0.2 for all). Conclusion: The use of a separation protocol in children and adolescents admitted for suicidal behavior is a widespread practice in France, despite the deprivation of liberty it implies. This raises the question of the relevance and usefulness of such a practice.